Photonics-Assisted Multi-Band Microwave Receiver Based on Spectrum Analysis and Coherent Channelization - Huang, Huan; Zhang, Chongfu; Zheng, Wei; Chen, Yong; Yang, Haifeng; Yi, Zichuan; Chi, Feng; Qiu, Kun (Frontiers in Physics, 2020)
Due to the limitation of analog-to-digital/digital-to-analog converters, photonics-assisted channelized receivers are thought to be a promising approach to receiving wideband microwave signals. Herein, based on the spectrum analysis and the coherent channelization, we develop a photonics-assisted channelized receiver for multi-band microwave signals. In the proposed channelized receiver, the instantaneous spectral analysis is introduced to determine the frequencies and bandwidth of a dynamic wideband signal. The dynamic wideband signal is then received by a multi-band coherent channelizer. By exploiting transparency of the optoelectronic devices, we equivalently build a multiband coherent channelizer that can work for dynamic microwave signals, where a few optoelectronic devices are required. Compared with the existing coherent channelizers, the operative bandwidth of the proposed multi-band coherent channelizer is much larger (up to 28 GHz). The proposed photonics-assisted channelized receiver doesn't need tunable optical comb generators and RF sources, and it also doesn't require knowing the spectrum information in advance. Moreover, the designed example of the proposed photonics-assisted channelized receiver for a 4 GHz original signal in 2 30 GHz microwave bands is given and discussed. The spectrum information of the dynamic original signals is obtained by monitoring the optical power in each sub-channel. We verify the feasibility of the multi-band coherent channelizer by channelizing two 4 GHz linearly-chirped signals with center frequencies of 4 GHz and 28 GHz into four 1 GHz sub-channels, respectively.